DISEMINASI KERUKUNAN UMAT BERAGAMA MODEL PESANTREN MAHASISWA DI PURWOKERTO - Moh Roqib (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This paper captures the tolerance of religious community as a dis- semination model implemented by an-Najah Islamic Boarding School for University Students motored by Kiai (Islamic Expert) and followed by Santri (Islamic Boarding School students). There were two dissemination approaches that had been conducted by an-Najah, they were academic and direct approaches through daily life. In terms of academic approach, it was conducted through Islamic studies such as reviewing classical Is- lamic book ( Kitab Kuning ) as the general characteristic of Islamic board- ing school reference, seminar, and dialogue with Moslem and non-Mos- lem scholars. Besides of those Islamic studies, an-Najah students were also taught about the nature of tolerance to face the diverse opinions and beliefs of other religions. In addition, an-Najah students were also intro- duced the diversity as well as the value of tolerance in living laboratory in the form of life skill training and community service involving the stu- dents and youth interfaith cooperation. The process of tolerance dissemi- nation had been conducted regularly and incidentally. Therefore, those practices could be maintained as a routine activity. To sum up, the pri- mary theoretical and practical studies implemented in Islamic boarding school could broaden the insightful perspective and pure heart as what was established through the Islamic boarding school tradition in line with the value of prophetic education.